(untitled) (Dhaka University Journal of Science, 2019)
The main aim of this paper is to find potential sources that affect maternal health care seeking behavior of women of urban areas in period around the birth of their children using data extracted from Bangladesh Urban Health Survey 2013. To examine the maternal health care seeking behavior among women,antenatal care, place of delivery and postnatal care are considered as dependent variables and several demographic and socio-economic factors are included as independent variable. The study reveals that the recent migrant women and slum dwellers have a tendency of being disadvantaged in context of maternal health care. There is still plenty of room to work on maternal health care among women in urban areas especially among recent migrants so that significant improvement can be initialized to achieve an equity in overall health care system in Bangladesh. Dhaka Univ. J. Sci. 67(2): 131-138, 2019 (July)